The relationship between boredom proneness, the behavioral inhibition system, and anxiety in college students: variable-centered and person-centered analytic approaches - Zhao, Mengmeng; Wang, Ruixin; Zhao, Zhenyu; Li, Lina; Luo, Hongge; Wu, Lei (Frontiers in Psychology, 2024)
Objective To explore the relationship among boredom proneness, the behavioral inhibition system, and anxiety among college students based on variable-centered and person-centered analytic approaches. Methods A questionnaire survey was conducted on 1,102 college students from a university in Hebei Province using the Boredom Proneness Questionnaire (BPQ) for College Students, the Behavioral Inhibition System Scale (BIS), and the General Anxiety Disorder-7 scale (GAD-7). Results The results reveal that boredom proneness was negatively correlated with scores on the behavioral inhibition system (r = −0.100, p < 0.01), and positively correlated with anxiety (r = 0.457, p < 0.001), while the behavioral inhibition system was positively correlated with anxiety (r = 0.086, p < 0.01). In the variable-centered analyses study, it was found that the behavioral inhibition system partially mediated the association between boredom proneness and anxiety. In the person-centered analyses study, three subtypes were identified: the high boredom-low inhibition group (9.35%), the moderate boredom-inhibition group (66.70%), and the low boredom-high inhibition group (23.95%). Individuals in these subtypes showed significant differences in anxiety scores (F = 4.538, p < 0.05), with the low boredom-high inhibition group scoring the highest. Conclusion The results showed that the behavioral inhibition system partially mediates the relationship between boredom proneness and anxiety in college students; boredom proneness and the behavioral inhibition system exhibit group heterogeneity, with distinct classification features closely related to anxiety.